2012
DOI: 10.1038/ncb2527
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin nucleotide status controls Sas-4-dependent pericentriolar material recruitment

Abstract: Regulated centrosome biogenesis is required for accurate cell division and for maintaining genome integrity1. Centrosomes consist of a centriole pair surrounded by a protein network known as pericentriolar material (PCM)1. PCM assembly is a tightly regulated, critical step that determines a centrosome’s size and capability2–4. Here, we report a role for tubulin in regulating PCM recruitment via the conserved centrosomal protein Sas-4. Tubulin directly binds to Sas-4; together they are components of cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…melanogaster Cnn is necessary for the formation of the centrosomal PCM during embryogenesis (Megraw et al 1999;Vaizel-Ohayon and Schejter 1999;Eisman et al 2009), gametogenesis (Li et al 1998;Yamashita et al 2003;Eisman et al 2009), asymmetric larval neuroblast divisions, and mitosis in tissue culture cells (Megraw and Kaufman 2000;Dobbelaere et al 2008). Additionally, Cnn is required to maintain the centriole pair at the center of the PCM (Lucas and Raff 2007) and is an important determinant of centrosome size at mitosis Gopalakrishnan et al 2012). However, Cnn has been shown to be essential only for early embryogenesis and spermatogenesis as nucleation of MTs by chromatin and spindle-associated mechanisms found in many eukaryotes (Luders et al 2006;Luders and Stearns 2007;O'Connell and Khodjakov 2007) are sufficient for the development of sterile adult flies (Megraw et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster Cnn is necessary for the formation of the centrosomal PCM during embryogenesis (Megraw et al 1999;Vaizel-Ohayon and Schejter 1999;Eisman et al 2009), gametogenesis (Li et al 1998;Yamashita et al 2003;Eisman et al 2009), asymmetric larval neuroblast divisions, and mitosis in tissue culture cells (Megraw and Kaufman 2000;Dobbelaere et al 2008). Additionally, Cnn is required to maintain the centriole pair at the center of the PCM (Lucas and Raff 2007) and is an important determinant of centrosome size at mitosis Gopalakrishnan et al 2012). However, Cnn has been shown to be essential only for early embryogenesis and spermatogenesis as nucleation of MTs by chromatin and spindle-associated mechanisms found in many eukaryotes (Luders et al 2006;Luders and Stearns 2007;O'Connell and Khodjakov 2007) are sufficient for the development of sterile adult flies (Megraw et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When expressed in Drosophila embryos, either Sas-4 alone or a mutant form of Asl able to bind Sas-4 but not Plk4 can promote formation of acentriolar PCM aggregates that nucleate cytoplasmic microtubules (Dzhindzhev et al 2010). Moreover, Sas-4 null mutant flies show a reduction of PCM components in testes (Gopalakrishnan et al 2011(Gopalakrishnan et al , 2012. This reflects the ability of Sas-4 to form complexes with CNN and Dplp; centrosomes with mutant Sas-4 unable to form such complexes have reduced PCM (Dzhindzhev et al 2010;Gopalakrishnan et al 2011).…”
Section: Pcm Assemblymentioning
confidence: 99%
“…This reflects the ability of Sas-4 to form complexes with CNN and Dplp; centrosomes with mutant Sas-4 unable to form such complexes have reduced PCM (Dzhindzhev et al 2010;Gopalakrishnan et al 2011). A double mutation in Sas-4 protein se-quence that abolishes its binding to tubulin enhances centrosomal protein complex formation leading to abnormally large centrosomes and asters (Gopalakrishnan et al 2012). Thus, tubulin binding may interfere with Sas-4-mediated PCM assembly.…”
Section: Pcm Assemblymentioning
confidence: 99%
“…When PCM is not recruited, centrioles are unstable, and thus no functional centrosomes are generated (5,6). Although initial proteomic studies suggested PCM to be an amorphous cloud composed of more than a 100 different proteins (7), recent superresolution microscopy of fly and human centrosomes have indicated key centrosomal proteins essential for centrosome biogenesis to be organized into distinct spatial compartments before appearing as a PCM cloud surrounding the centriole (6,(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…During the course of these studies, we and others have reported that Sas-4/CPAP, a protein essential for centriole formation was found to interact with several centrosomal and PCM proteins including Cnn, Asl, D-PLP, γ-TuRC, SIL, Cep135, Cep120, and tubulin dimers (5,6,(14)(15)(16). In Drosophila, the N-terminal domain of Sas-4 provides a scaffolding site for cytoplasmic protein complexes (hereafter referred to as Sas-4-PCM scaffold) and tethers the components of Sas-4-PCM scaffold to a centrosome matrix via its C terminus (6).…”
mentioning
confidence: 99%